2014
DOI: 10.1590/s1677-5538.ibju.2014.04.11
|View full text |Cite
|
Sign up to set email alerts
|

A new problem in inflammatory bladder diseases: Use of mobile phones!

Abstract: ARTICLE INFO ______________________________________________________________ ______________________Purpose: Technological developments provide a lot of conveniences to our lives. This issue is one of the risks that arise along with these conveniences. In our study we tried to understand the impact of electromagnetic waves from mobile phones on bladder tissue. Materials and Methods: Twenty-one adult male albino rats were divided into three equal groups. Group 1 was exposed to electromagnetic wave for 8 hours per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The simultaneous presence of phages, that inhibit excessive reactive oxygen species (54), and Gc protein-derived Macrophage Activating Factor that stimulates human blood macrophages (59), prevents these harmful effects of electromagnetic radiations on macrophages. The simultaneous presence of phages and Gc protein-derived Macrophage Activating Factor leads to optimization of immune system function at the same time preventing inflammation (54), a threatening pathologic feature that accompanies dysregulated immune responses to ionizing radiation as well as to mobile telecommunication electromagnetic radiations (60). Co-culturing Arthrospira platensis with the probiotic blend in the same aqueous medium allows exchange of biological information through horizontal gene transfer and quantum entanglement as specifically demonstrated for protective responses to radiations (50).…”
Section: Resultsmentioning
confidence: 99%
“…The simultaneous presence of phages, that inhibit excessive reactive oxygen species (54), and Gc protein-derived Macrophage Activating Factor that stimulates human blood macrophages (59), prevents these harmful effects of electromagnetic radiations on macrophages. The simultaneous presence of phages and Gc protein-derived Macrophage Activating Factor leads to optimization of immune system function at the same time preventing inflammation (54), a threatening pathologic feature that accompanies dysregulated immune responses to ionizing radiation as well as to mobile telecommunication electromagnetic radiations (60). Co-culturing Arthrospira platensis with the probiotic blend in the same aqueous medium allows exchange of biological information through horizontal gene transfer and quantum entanglement as specifically demonstrated for protective responses to radiations (50).…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies urinary bladder [12] and kidney damages [19] were observed on mature rats after exposing EMW for 20 days. In an another study EMW exposure was applied to the rats in prenatal period and observed harmful effect on the kidney development [20].…”
Section: Discussionmentioning
confidence: 96%
“…However, the effects of EMW's on urinary bladder are limited [12]. The incidance of sterile bladder diseases such as interstitial cystitis and overactive bladder syndrome has beeen increasing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The simultaneous presence of phages, that inhibit excessive reactive oxygen species formation (Górski et al, 2017) and Gc protein-derived Macrophage Activating Factor that stimulates human blood macrophages (Pacini et al, 2012), prevents these harmful effects of radiations on macrophages. In addition, the simultaneous presence of phages and Gc protein-derived Macrophage Activating Factor leads to optimization of immune system function at the same time preventing inflammation (Górski et al, 2017), a threatening pathologic feature that accompanies dysregulated immune responses to ionizing radiation as well as to mobile telecommunication electromagnetic fields (Koca et al, 2014). Co-culturing Arthrospira platensis with the probiotic blend in the same aqueous medium allows exchange of biological information through horizontal gene transfer and quantum entanglement as specifically demonstrated for protective responses to radiations (Mothersill et al, 2018).…”
Section: Rationale For the Co-culture Of Arthrospira Platensis With Probioticsmentioning
confidence: 99%